Learner abilities, characteristics, and background as determinants of chemistry achievement - Gonzales, Flordeliza Vendiola (1989)
The study examined the relationship between chemistry achievement and learner abilities, characteristics, and background. Itwas found that there was a significant positive correlation between chemistry achievement and mental, mathematical, spatial, language usage, and verbal reasoning abilities. The more favorable a student's perception to his chemistry teacher, the lower is his chemistry achievement. Females perform better than males in chemistry. Students who graduated from private high schools achieve better in chemistry than public high school.
Thesis (M.A. Chemistry Education)--University of the Philippines, Diliman.
Keywords: Chemistry -- Ability testing -- Philippines -- Dumaguete City (Negros Oriental); Academic achievement -- Philippines -- Dumaguete City (Negros Oriental); College students -- Philippines -- Dumaguete City (Negros Oriental)